TO COMPARE EFFICACY BETWEEN CRYOTHERAPY AND MITOMYCIN MICRONEEDLING FOR THE TREATMENT OF PLANTAR WARTS - Afsar Khan, Faheema; Majid Hussain; Bushra muzaffar Khan; Saima afsar; Mairah shafique; Sami ul Haq; Nadia Akbar; Adeel Siddique (Journal of Ayub Medical College Abbottabad, 2023)
Background: Cryotherapy is a common destructive treatment modality for treating plantar warts that results in blistering and scarring. Mitomycin an antitumor drug with antiviral property is a safe, better and a promising option for treating plantar warts. Objective was to compare efficacy of cryotherapy and mitomycin microneedling in the management of plantar warts. It was a randomized controlled trial conducted at the Skin Department CMH Abbottabad from 1st May to 31st December 2021. Methods: The study included 60 patients with plantar warts. Each group with 30 patients. Random tables were used to determine the distribution of patients within each group. Group A received mitomycin microneedling (1u/ml) repeated every 3 weeks. Group B was prescribed liquid nitrogen cryotherapy. The freeze-thaw cycle was 20 secs and repeated every 2 weeks. Both groups were treated for 4 months duration were. For analysis of data, SPSS version 21.0 was used. Efficacy was compared by the application of Chi-square test between the two groups. p<0.05 was considered statistically significant. Results: Mitomycin microneedling completely cured 76.7% of patients, while cryotherapy was effective for only 56.7%. Complete remission was observed after two to three sessions of mitomycin microneedling while average of 4 sessions of cryotherapy were required for complete remission. In general, microneedling with mitomycin had better tolerance, pain being the commonest adverse effect. Conclusion: Plantar warts can be effectively treated with mitomycin microneedling. Treatment of plantar warts with this method is more effective, requires fewer sessions, and may take less time to complete.